2002
DOI: 10.1152/jn.00187.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sound-Level-Dependent Representation of Frequency Modulations in Human Auditory Cortex: A Low-Noise fMRI Study

Abstract: Recognition of sound patterns must be largely independent of level and of masking or jamming background sounds. Auditory patterns of relevance in numerous environmental sounds, species-specific vocalizations and speech are frequency modulations (FM). Level-dependent activation of the human auditory cortex (AC) in response to a large set of upward and downward FM tones was studied with low-noise (48 dB) functional magnetic resonance imaging at 3 Tesla. Separate analysis in four territories of AC was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 80 publications
14
97
5
Order By: Relevance
“…This is in line with previous studies on sound intensity (Hegerl et al 1994;Jäncke et al 1998;Mohr et al 1999;Hall et al 2001;Bilecen et al 2002;Brechmann et al 2002;Gutschalk et al 2002;Hart et al 2002Hart et al , 2003Lasota et al 2003;Mulert et al 2005;Sigalovsky and Melcher 2006;Langers et al 2007;Ernst et al 2008). Probably due to the comparatively large number of participants in our study and the large examined range of levels and corresponding perceived loudness, it was possible to specify that the volume of activation increases exponentially and the percent signal change from baseline almost linearly with sound pressure level in all examined stages of the auditory pathway.…”
Section: Psychoacoustics In Different Hearing Environmentssupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with previous studies on sound intensity (Hegerl et al 1994;Jäncke et al 1998;Mohr et al 1999;Hall et al 2001;Bilecen et al 2002;Brechmann et al 2002;Gutschalk et al 2002;Hart et al 2002Hart et al , 2003Lasota et al 2003;Mulert et al 2005;Sigalovsky and Melcher 2006;Langers et al 2007;Ernst et al 2008). Probably due to the comparatively large number of participants in our study and the large examined range of levels and corresponding perceived loudness, it was possible to specify that the volume of activation increases exponentially and the percent signal change from baseline almost linearly with sound pressure level in all examined stages of the auditory pathway.…”
Section: Psychoacoustics In Different Hearing Environmentssupporting
confidence: 90%
“…Several neuroimaging studies on the neural coding of sound intensity in the human auditory system have commonly shown that neural activation increases as a function of sound intensity in auditory areas (Hegerl et al 1994;Jäncke et al 1998;Mohr et al 1999;Hall et al 2001, Bilecen et al 2002Brechmann et al 2002;Gutschalk et al 2002;Hart et al 2002Hart et al , 2003Lasota et al 2003;Mulert et al 2005;Sigalovsky and Melcher 2006;Langers et al 2007;Ernst et al 2008;Röhl and Uppenkamp 2010;Röhl et al 2011). There is still some dispute, however, over the precise location of intensity coding, e.g., whether it is more related to primary areas like the Heschl's gyrus as described by Hart et al (2002) or more related to secondary auditory areas like the Planum Temporale as described by Gutschalk et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher pitch-direction thresholds were found in patients with right (but not left) auditory cortex lesions for two 100 ms tones presented with 800 ms between them (Johnsrude, Penhune, & Zatorre, 2000). Both PET and fMRI studies provide evidence for right lateralization of processing slow (500 ms) frequency modulated sweeps (Brechmann, Baumgart, & Scheich, 2002;Poeppel, et al, 2004). Similarly, the results of an fMRI study showed greater activation in the left hemisphere when participants listened to meaningless speech that contained the rapid frequency changes of normal phonological information and greater activation in the right hemisphere when the same participants listened to the slower, global changes in fundamental frequency that communicate prosody (Meyer, Alter, Friederici, Lohmann, & von Cramon, 2002).…”
Section: Lateralization Of Auditory Processingmentioning
confidence: 92%
“…the auditory cortex (AC) [3]. The alternative approach is to define subject-specific regions of interest (ROI) by using a combination of anatomical landmarks and clusters of brain activation obtained in functional imaging studies [1,6]. So far, the observer-dependent and time-consuming nature of the manual delineation of ROI represents a tradeoff for the advantages (better spatial specificity and improved statistical power) of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we use our model for segmentation of the landmarkoriented auditory ROI described in [1,6]. This provides a reliable surface-based comparison of auditory functional activations across subjects.…”
Section: Introductionmentioning
confidence: 99%